Iranian herbal distillates (Hydrosols): From traditional beverages to modern industrial applications - Ghahremaninejad, Farrokh; Nazari, Hamid; Bussmann, Rainer W; Jalali, Sahar; Mohammadi, Mohammad; Joharchi, Mohammadreza; Mousavi Zahed, Maryam; Alirezaei, Zahra (Ethnobotany Research and Applications, 2026)
Background: Iranian herbal distillates are traditional aqueous products of hydro-distillation with centuries of use in Persian medicine, culinary practices, and cultural rituals. They are documented in historical texts such as those by Avicenna and remain widely employed as beverages, folk remedies, and flavoring agents. This study aims to comprehensively document the botanical sources, traditional uses, production methods, and industrial potential of Iranian hydrosols through an integrated approach combining systematic literature review and extensive ethnobotanical fieldwork. Methods: A systematic literature search was conducted across Scopus, PubMed, Web of Science, and Google Scholar. Field surveys were carried out between September 2023 and September 2025, including visits to three industrial distilleries in Shiraz and Kashan, and surveys of 35 herbal shops and traditional markets across five Iranian cities. Data on plant species, production practices, uses, and market status were collected, taxonomically verified, and analyzed using R. Results: Fifty-three plant species from 28 families were documented, with Lamiaceae, Asteraceae, and Apiaceae being the most represented. Aerial parts were the most frequently used plant material. The most commonly reported bioactivities included antimicrobial, antioxidant, and anti-inflammatory effects. Industrial potential was highest in the sectors of functional beverages, flavoring agents, and cosmetics. Conclusions: Iranian herbal distillates represent a diverse and culturally significant resource with considerable potential for applications in functional foods, cosmetics, and phytopharmaceuticals. To support industrial scale-up, future efforts should focus on production standardization, clinical validation of bioactivities, and sustainable sourcing practices. Keywords: Ethnobotany, Hydrosols, Functional Beverages, Industrial Applications, Traditional Medicine.